Lectures on Antitrust Economics, Chapter 3: Horizontal Mergers - Michael D. Whinston (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
In this chapter our attention turns to horizontal merger policy. The Sherman Act's prohibition on "contracts, combinations, and conspiracies in restraint of trade," whose application to price fixing we discussed in Chapter 2, also applies to horizontal mergers, but with an important difference: horizontal mergers are evaluated by the courts under a Rule of Reason analysis based on the presumption that they often have important efficiency benefits. In addition, the Clayton Act's Section 7 includes a more specific prohibition on mergers where the effect may be "substantially to lesson competition, or to tend to create a monopoly." Despite the potential for efficiencies arising from horizontal mergers, from the 1950's through the 1970's the U.S. courts were extremely hostile toward them, often condemning horizontal mergers in markets that were and would remain very unconcentrated. Since 1980, however, with a more conservative judiciary and an increasing influence of economic reasoning, horizontal merger policy has become much more permissive. During this same period, there has also been substantial progress in economists' ability to analyze proposed horizontal mergers. In what follows we will review this progress, while also noting some of the significant open questions that remain.
Keywords: 330; Konzentrationspolitik; Kartellrecht; Preisabsprache; Fusionskontrolle; USA